The interaction between embodiment and empathy in facial expression recognition. Issue 2 (25th January 2018) - Jospe, Karine; Flöel, Agnes; Lavidor, Michal
Abstract: Previous research has demonstrated that the Action-Observation Network (AON) is involved in both emotional-embodiment (empathy) and action-embodiment mechanisms. In this study, we hypothesized that interfering with the AON will impair action recognition and that this impairment will be modulated by empathy levels. In Experiment 1 ( n  = 90), participants were asked to recognize facial expressions while their facial motion was restricted. In Experiment 2 ( n  = 50), we interfered with the AON by applying transcranial Direct Current Stimulation to the motor cortex. In both experiments, we found that interfering with the AON impaired the performance of participants with high empathy levels; however, for the first time, we demonstrated that the interference enhanced the performance of participants with low empathy. This novel finding suggests that the embodiment module may be flexible, and that it can be enhanced in individuals with low empathy by simple manipulation of motor activation.